Stereotactic Body Radiotherapy for Localized Ureter Transitional Cell Carcinoma: Three Case Reports - Yoshiyasu Maehata; Kengo Kuriyama; Shinichi Aoki; Masayuki Araya; Kan Marino; Hiroshi Onishi (Case Reports in Urology)
The gold standard management for ureter transitional cell carcinoma (UTCC) is radical nephroureterectomy with excision of the bladder cuff. However, some patients cannot undergo this procedure for several reasons. In the case reports described herein, we performed stereotactic body radiotherapy (SBRT) on three patients with inoperable or surgery-rejected localized UTCC. Two out of the three patients did not develop local recurrence or distant metastasis during the observation period. However, recurrence was detected in the bladder of one patient 22 months after the treatment. No acute or late adverse events occurred in any of the three patients. SBRT may become one of the treatment options for inoperable or surgery-rejected UTCC patients.